Disorders of childhood development and psychopathology - Parritz, Robin Hornik; Troy, Michael F.
"To provide you with a meaningful framework for learning and understanding, Parritz and Troy's Disorders of Childhood, 4th edition, is written with the whole child in mind and presents disorders in the context of typical development and developmental pathways. Multiple themes recur throughout the text: the continuity between typical and atypical development, risk and resilience, complex models of psychopathology, children in relationships over time, children in larger social contexts (ethnic backgrounds, neighborhoods, cultures), and the holistic nature of development (thinking about the child's abilities and strengths in addition to the disorder or areas of struggle). This developmental psychopathology approach, which reflects the most up-to-date understanding of child and adolescent psychopathology, will teach you to think about disorders in terms of the individual children who are coping with distress and dysfunction" -- Provided by publisher